THU0614 Forewarned Is Forearmed? Risk Communication during The Commencement of Methotrexate; Presenting The Clinicians' & Patients' Perspectives. (15th July 2016) - Hope, H.F.; Cronin, C.; Jacklin, C.; Cordingley, L.; Hyrich, K.; Verstappen, S.M.
Abstract : Background: Methotrexate (MTX) is the first-line treatment for rheumatoid arthritis (RA). Previously, we have shown that patient concerns about side effects were associated with early MTX non-adherence. The first opportunity to address these concerns is during the initial clinical consultation. A crucial factor in determining if a patient initiates and adheres to MTX could be if side effects are adequately addressed in the initial clinical consultation. Objectives: The aims of this research were to evaluate from a patient's and rheumatologist's perspective i) the extent to which MTX risks are addressed during consultation and ii) possible factors constraining discussion of side effects Methods: This is a mixed methods study. To evaluate the patient's perspective an online survey was co-constructed with the National Rheumatoid Arthritis Society in the UK. The survey gathered basic demographic information and included items relevant to risk communication during the initial consultation, including the extent to which side effects were discussed. The responses of patients who reported commencing methotrexate were selected for descriptive analyses. To evaluate the rheumatologist's perspective interviews were conducted with rheumatologists. A sampling strategy ensured the views of senior and junior clinicians from different clinical settings across the UK were represented. The semi-structured topic guide contained questions about the MTX commencement consultation, including key information patients should have, how this was communicated and barriers to communication. The interviews were audio-recorded, transcribed and analysed qualitatively using Framework Analysis. Results: Overall 648 people with RA completed the online survey, (83% female & 63% aged between 46 and 65 years). Eleven rheumatologists with one to 25 years experience as consultants and four trainees consented to be interviewed. The majority of respondents to the patient survey (62%) reported their initial consultation was less than 30 minutes. Of the 587 respondents who reported commencing methotrexate 16% reported they discussed side effects very little and 16% did not discuss side effects with their rheumatologist at all. Rheumatologists reported that patients should be informed about the side effects of methotrexate, however clinicians (n=9) were concerned about overloading the patient with information. Particular barriers to discussing side effects included; limited consultation time and concurrent diagnosis of RA and methotrexate commencement. These barriers were perceived as particularly acute when patients were unprepared for the diagnosis or had pre-existing negative beliefs about methotrexate. Conclusions: Patients and rheumatologists separately reported side effects were not always discussed when commencing methotrexate, and barriers to communication were identified. Given that suspected side effects are a reason for non-adherence to methotrexate these need to be addressed. The development of new tools acceptable to patients and clinicians that facilitate the discussion of side effects, without extending the clinical consultation, may improve patient understanding and adherence. Disclosure of Interest: None declared